The sign and magnitude of tree–grass interaction along a global environmental gradient - Mazía, Noemí (2016)
Fil: Mazía, Noemí. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Producción Vegetal. Buenos Aires, Argentina.